2010
DOI: 10.1007/s00203-010-0603-7
|View full text |Cite
|
Sign up to set email alerts
|

First description of a laccase-like enzyme in soil algae

Abstract: Laccases (EC 1.10.3.2) are versatile multi-copper oxidases so far found in higher plants, fungi, insects, prokaryotes and lichens. In the present study, the production of an extracellular laccase-like enzyme by the coccoid green soil alga Tetracystis aeria was investigated and the enzyme was partly characterized, thereby providing the first description of a laccase-like enzyme in soil algae. Enzyme production in algae cultures was considerably increased by addition of the fungal laccase inducer copper sulphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…It is known that many algae may grow well heterotrophically and produce glucan hydrolases like chitinase and laccase (Reisser 2007;Otto et al 2012) and even degrade phenolic compounds (Semple et al 1999). When these substrates effectively fuel the algal metabolism, ecologically relevant growth of algae in aphotic ecosystems, including rock, may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that many algae may grow well heterotrophically and produce glucan hydrolases like chitinase and laccase (Reisser 2007;Otto et al 2012) and even degrade phenolic compounds (Semple et al 1999). When these substrates effectively fuel the algal metabolism, ecologically relevant growth of algae in aphotic ecosystems, including rock, may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, laccases have been isolated predominantly from plants and fungi. However, in recent years, the laccase toolbox has been expanding, with the enzymes also being detected in bacteria, insects, and algae . The physiological functions of laccases from different sources are highly diverse.…”
Section: Laccasesmentioning
confidence: 99%
“…Since then, characteristics of laccases from other insect species have been determined . In the silkworm, Bombyx mori , a cuticle laccase is highly expressed a few hours after ecdysis . This 70 kDa dimer polypeptide plays an important role in cuticle sclerotization .…”
Section: Occurrence Of Laccases In Living Organisms and Their Physiolmentioning
confidence: 99%
“…44 This 70 kDa dimer polypeptide plays an important role in cuticle sclerotization. 44 Coy et al 65 reported the functional expression of two recombinant laccase genes of the insect termite (Reticulitermes flavipes), designated as RfLacA and RfLacB, using a baculovirus-insect expression system. Oxidation of cuticular catechols, assisted by phenoloxidases, tyrosinase, and laccases, is essential for cuticle hardening and pigmentation in many insects, such as Riptortus pedestris, Nysius plebeius, and Megacopta punctatissima.…”
Section: Occurrence Of Laccases In Living Organisms and Their Physiolmentioning
confidence: 99%